PENGARUH BRAND TRUST TERHADAP LOYALITAS MEREK PADA PENGGUNA PRODUK-PRODUK AMAL USAHA MUHAMMADIYAH DI KOTA YOGYAKARTA - Riska Amalia (STAI Syubbanul Wathon Magelang, 2017)
The large amount of competition in the business world today makes every company must have a specific strategy to deal with it. Companies must be able to survive and even continue to grow. One way is to maintain existing customers. Companies must be able to maintain customer loyalty. Trust in the brand is part of the consumer perception that the goods or services purchased or used can be relied upon and provide guarantees that they are not detrimental. The design of this study was designed in the form of field research, where the research data and information were obtained from research field activities. The approach used in this study is a quantitative approach to the type of causality. The sampling technique uses the judgment sampling method, namely sampling with certain considerations. The sample of this study was 69 respondents. The data analysis uses Multiple Linear Regression (t-Test and F Test) with the help of SPSS for Windows 15.0. Based on the results of the study, it can be seen that brand characteristics variables, company characteristics and consumer-brand characteristics have a significant influence on brand loyalty both partially and simultaneously.